Protecting the Auckland Harbour Bridge, New Zealand – developing a 40-year coatings maintenance plan. Issue 4 (19th July 2019) - El Sarraf, Raed; Barker, Hannah
Abstract : The Auckland Harbour Bridge (Auckland, New Zealand), built in 1959 and widened in 1969, has approximately 125 000 m 2 of external steel surfaces that have previously been maintained using a 'spot repair and overcoat' approach. This has been carried out since 1998 under a performance-specified maintenance contract using moisture-cured urethane coatings. In 2017, the Auckland Harbour Bridge Alliance embarked on a study to review the existing coatings maintenance regime and investigate alternative maintenance strategies. This paper summarises the findings of this investigation, from which a 40-year coatings maintenance plan was developed using net present value life-cycle cost analysis of zone painting. The maintenance plan was developed to achieve the lowest whole-of-life cost while meeting environmental protection requirements.